Effectiveness of eHealth interventions for the promotion of physical activity in older adults: a systematic review - Muellmann, Saskia; Möllers, Tobias (Preventive medicine, 2018)
Regular physical activity (PA) is central to healthy ageing. However, only a minority of older adults currently meet the WHO-recommended PA levels. The aim of this systematic review is to compare the effectiveness of eHealth interventions promoting PA in older adults aged 55years and above with either no intervention or a non-eHealth intervention (review registration: PROSPERO CRD42015023875). Eight electronic databases were searched to identify experimental and quasi-experimental studies examining the effectiveness of eHealth interventions for PA promotion in adults aged 55years and above. Two authors independently selected and reviewed references, extracted data, and assessed study quality. In the search, 5771 records were retrieved, 20 studies met all inclusion criteria. Studies varied greatly in intervention mode, content, duration and assessed outcomes. Study quality ranged from poor to moderate. All interventions comprised tailored PA advice and the majority of interventions included goal setting and feedback, as well as PA tracking. Participation in eHealth interventions to promote PA led to increased levels of PA in adults aged 55years and above when compared to no intervention control groups, at least in the short term. However, the results were inconclusive regarding the question of whether eHealth interventions have a greater impact on PA behavior among older adults than non-eHealth interventions (e.g., print interventions). eHealth interventions can effectively promote PA in older adults aged 55years and above in the short-term, while evidence regarding long-term effects and the added benefit of eHealth compared to non-eHealth intervention components is still lacking.